Obtaining magnetic and electric information on organic systems using electron spin resonance - Walmsley, L. [UNESP] (My University, 2009)
A very rich diversity of magnetic ordering can be found in organic systems, and in many of these systems an electron spin resonance (ESR) line can be observed even at room temperature. This fact allows a great deal of information to be obtained for a broad range of temperatures. Among other factors, information can be collected about the surroundings of the magnetic moments, the mechanisms of relaxation of the magnetization, the interaction with other magnetic moments and if they are localized or delocalized. The possibility to compare the ESR magnetic data with data obtained from magnetic measurements using volume techniques like magnetization obtained from Vibrating Sample Magnetometers (VSM) or Superconductor Quantum Interference Device (SQUID) magnetometers, allows a detailed analysis of the magnetic systems under study. In certain special situations, for some particular geometrical conditions, the conductivity at the microwave frequency can also be obtained from the ESR line asymmetry, providing a simple and precise method of contactless conductivity measurements.